Titanium oxo-clusters: precursors for a Lego-like construction of nanostructured hybrid materials - Rozes, Laurence; Sanchez, Clément (Chemical Society reviews, 2011)
Titanium oxo-clusters, well-defined monodispersed nano-objects, are appropriate nano-building blocks for the preparation of organic-inorganic materials by a bottom up approach. This critical review proposes to present the different structures of titanium oxo-clusters referenced in the literature and the different strategies followed to build up hybrid materials with these versatile building units. In particular, this critical review cites and reports on the most important papers in the literature, concentrating on recent developments in the field of synthesis, characterization, and the use of titanium oxo-clusters for the construction of advanced hybrid materials (137 references).